Advancing flexible electronics and additive manufacturing. (1st June 2022) - Espera, Alejandro H.; Dizon, John Ryan C.; Valino, Arnaldo D.; Advincula, Rigoberto C.
Abstract: There is high interest in the synergism of thin-film and flexible electronics with additive manufacturing. This review primarily focuses on the prospective developments in convergence with flexible electronics manufacturing technologies. Specifically, this paper covers the latest 3D printing and hybrid manufacturing technologies, the utility of specific types of materials, their functionalization and characterization, post-processing and testing strategies toward fabricating robust and application-specific flexible electronics. Besides exploring the advances in this area of research—it also highlights the limitations and gaps that have been observed in the previous years that will challenge and offer opportunities for advancing research and development. Lastly, the future of 3D-printed flexible electronics is discussed in the aspects of customizability, scalability, and its game-changing and state-of-the-art potential for intelligent sensing, instrumentation, and wearables for various medical, engineering, and industrial applications.